I am stuck on this prblem (logarithms)

abel muroi

Junior Member
Joined
Jan 13, 2015
Messages
210
I was given the problem log5(x + 1) - log5(x - 1) = 2 and was told to solve for x

here is the work i have so far...

log5(x + 1) - log5(x - 1) = 2
log5((x + 1)/(x - 1)) = 2

Im not sure what to do next here, should i take the log of 2 as well? or should i divide log5 with 2?
 
I was given the problem log5(x + 1) - log5(x - 1) = 2 and was told to solve for x

here is the work i have so far...

log5(x + 1) - log5(x - 1) = 2
log5((x + 1)/(x - 1)) = 2

Im not sure what to do next here, should i take the log of 2 as well? or should i divide log5 with 2?


Hint: 2 = log525
 
1 = logN(N) for any valid base N.

wait i think i have it figured out, can you check if i did this right?

log x + log (x - 3) = 1
log (x2 - 3x) = log 0
x2 - 3x = 0
(x - 3) (x + 0) = 0

x = 3

did i do this correctly?
 
wait i think i have it figured out, can you check if i did this right?

log x + log (x - 3) = 1
log (x2 - 3x) = log 0
x2 - 3x = 0
(x - 3) (x + 0) = 0

x = 3

did i do this correctly?
No, you went backwards: log(1)=0, not log(0)=1!

If the log is the natural log [base e], then
log (x2 - 3x) = log e
x2 - 3x = e
 
No, you went backwards: log(1)=0, not log(0)=1!

If the log is the natural log [base e], then
log (x2 - 3x) = log e
x2 - 3x = e

So once i get the e, how can i factor x2 - 3x - e = 0?
 
Last edited:
how can i factor x^2 - 3x - e = 0?

Im not used to factoring an e in a equation, can someone show me the way of a mathematician?
 
What about the problem log x + log (x - 3) = 1

should i use log for 1?

In the "olden days" when I was studying math in college, when no base was specified for "log", the log was assumed to be a "common logarithm" with a base of 10.

So, log 100 = 2, since 100 = 102

So.....I would handle your problem this way:

log x + log (x - 3) = 1

log (x2[ - 3x) = log 101

x2 - 3x = 10

x2 - 3x - 10 = 0

Now....that factors nicely! Ball is in your court.
 
Top